Study on the Influence of Recycled Composite Micro Powder on the Performance of Mortar - Yu, Tao (International Journal of Materials Science and Technology Studies, 2025)
In the rapid urbanization process, the extensive development model of China's construction industry has led to excessive consumption of natural resources and intensified environmental. Its resource utilization has become an important topic for the sustainable development of the industry. This study proposes a composite admixture technology path to address the technical bottlene in the application of recycled micro-powder. By constructing a binary composite system of recycled concrete powder (RCP) and recycled brick powder (RBP), the characteristics and multi-age mechanical properties were systematically characterized and tested. The results show that compared with single RAP, the admixture of recycled micro-powder can significantly the mechanical properties of recycled mortar, among which the RCP: RBP = 8:2 group shows the best enhancement effect, with an increase in 2d compressive strength of 23.6% and an increase in flexural strength of 18.4%. The results show that the composite micro-pow system achieves a synergistic effect of micro-aggregate filling and volcanic ash activity through the gradient distribution of particle size, which effectively optimizes the microstructure of cement materials. The composite admixture technology framework established in this study not only improves the amount of recycled micro-powder admixture but also provides a new reference for the-value utilization of construction solid waste.